Dimethyl sulfoxide reductase of Escherichia coli: an investigation of function and assembly by use of in vivo complementation. - Sambasivarao, D (1991)
Dimethyl sulfoxide (DMSO) reductase of Escherichia coli is a membrane-bound, terminal anaerobic electron transfer enzyme composed of three nonidentical subunits. The DmsAB subunits are hydrophilic and are localized on the cytoplasmic side of the plasma membrane. DmsC is the membrane-intrinsic polypeptide, proposed to anchor the extrinsic subunits. We have constructed a number of strains lacking portions of the chromosomal dmsABC operon. These mutant strains failed to grow anaerobically on glycerol minimal medium with DMSO as the sole terminal oxidant but exhibited normal growth with nitrate, fumarate, and trimethylamine N-oxide, indicating that DMSO reductase is solely responsible for growth on DMSO. In vivo complementation of the mutant with plasmids carrying various dms genes, singly or in combination, revealed that the expression of all three subunits is essential to restore anaerobic growth. Expression of the DmsAB subunits without DmsC results in accumulation of the catalytically active dimer in the cytoplasm. The dimer is thermolabile and catalyzes the reduction of various substrates in the presence of artificial electron donors. Dimethylnaphthoquinol (an analog of the physiological electron donor menaquinone) was oxidized only by the holoenzyme. These results suggest that the membrane-intrinsic subunit is necessary for anchoring, stability, and electron transport. The C-terminal region of DmsB appears to interact with the anchor peptide and facilitates the membrane assembly of the catalytic dimer.